Prognostic implications of glycated hemoglobin in nondiabetic patients with acute coronary syndrome - Mohanty, Namita; Mishra, Debakanta; Acharya, Suvendu Sekhar; Kurian, Sijoy; Giri, Suprabhat (International Journal of Research in Medical Sciences, 2016)
Background: In nondiabetic patients with acute coronary syndrome, acute hyperglycemia is associated with adverse outcome. Whether this association is due merely to hyperglycemia as an acute stress response or whether longer-term glycometabolic derangements are also involved is uncertain. It was our aim to determine the association between chronic hyperglycemia (hemoglobin A1c (HbA1c) and outcome in nondiabetic patients with acute coronary syndrome. Methods: This observational study included consecutive patients (n=47) without known diabetes mellitus admitted with acute coronary syndrome (STEMI, NSTEMI, UA). HbA1c was measured on admission. The main outcome was MACE (major adverse cardiac events including death, cardiogenic shock, arrhythmia, heart failure). The patients were divided into 2 groups according to their HbA1c level (group 1 HbA1c<5.7%, group 2 HbA1c>5.7%). Results: There was no significant difference between baseline characteristics of both groups but complications were seen in higher number cases with HbA1c >5.7%. No significant difference in mortality was found. On multivariate logistic regression analysis HbA1c >5.7% was found to be an independent predictor of MACE. Conclusions: There was no significant difference between baseline characteristics of both groups but complications were seen in higher number cases with HbA1c>5.7%. No significant difference in mortality was found. On multivariate logistic regression analysis HbA1c>5.7% was found to be an independent predictor of MACE.